2004
DOI: 10.1111/j.1523-1755.2004.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal nitric oxide synthase inhibition sensitizes the tubuloglomerular feedback mechanism after volume expansion

Abstract: These results suggest that a functioning nitric oxide system, especially through the nNOS, is important in mediating normal renal responses and that increased production of and/or sensitivity to nitric oxide during sustained VE plays an important role in the adaptive mechanism of the tubuloglomerular feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 38 publications
(49 reference statements)
1
37
1
1
Order By: Relevance
“…However, micropuncture experiments (41) showed that the tubuloglomerular feedback (TGF), which is an important mechanism in the control of GFR and blood pressure regulation, is reset during volume expansion in a paradoxical way to a much higher sensitivity and activity in the hydronephrotic kidney. The regulation of the sensitivity and reactivity of the TGF is intimately coupled to NO production in the macula densa (4) and the same kind of TGF resetting has been described in animal models for hypertension (11,49,59).…”
mentioning
confidence: 74%
“…However, micropuncture experiments (41) showed that the tubuloglomerular feedback (TGF), which is an important mechanism in the control of GFR and blood pressure regulation, is reset during volume expansion in a paradoxical way to a much higher sensitivity and activity in the hydronephrotic kidney. The regulation of the sensitivity and reactivity of the TGF is intimately coupled to NO production in the macula densa (4) and the same kind of TGF resetting has been described in animal models for hypertension (11,49,59).…”
mentioning
confidence: 74%
“…Interestingly, Brown et al (39) have shown that increased NO activity desensitizes the tubuloglomerular feedback mechanism, which could explain the increased GFR in the diabetic animals observed after L-arginine injection (40). The inverse mechanism could be responsible for the decreased GFR in the control animals observed after inhibition of NO production.…”
Section: Discussionmentioning
confidence: 99%
“…The responsiveness of the TGF mechanism involves the action of different vasoactive substances, of which NO is an important determinant. 20,26 Hydronephrotic kidneys display reduced renal NO availability, which is associated with a sensitized TGF response. 5 In the present study, unspecific NOS inhibition with L-NAME did not cause any significant constriction of AAs from the hydronephrotic kidneys of wild-type mice, but the controls constricted Ϫ12% and the AAs of the contralateral kidney constricted as much as Ϫ43% after 15 minutes of treatment.…”
Section: Discussionmentioning
confidence: 99%